2023
DOI: 10.1001/jamanetworkopen.2023.1887
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Diabetic Retinopathy in Pediatric Type 2 Diabetes

Abstract: ImportanceType 2 diabetes (T2D) is increasing globally. Diabetic retinopathy (DR) is a leading cause of blindness in adults with T2D; however, the global burden of DR in pediatric T2D is unknown. This knowledge can inform retinopathy screening and treatments to preserve vision in this population.ObjectiveTo estimate the global prevalence of DR in pediatric T2D.Data SourcesMEDLINE, Embase, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), the Cochrane Library, the Web of Science, and the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…The proportion of malnourished patients assessed by GLIM, PNI, and CONUT was higher in males. In the current study, gender differences in DR and malnutrition are inconclusive [31][32][33]. In our study, patients with DR had a lower BMI, which was contrary to the Yin et al's study [30].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The proportion of malnourished patients assessed by GLIM, PNI, and CONUT was higher in males. In the current study, gender differences in DR and malnutrition are inconclusive [31][32][33]. In our study, patients with DR had a lower BMI, which was contrary to the Yin et al's study [30].…”
Section: Discussioncontrasting
confidence: 94%
“…In our study, patients with DR had a lower BMI, which was contrary to the Yin et al's study [30]. However, the current meta-analysis showed that there was no difference in the prevalence of DR between obese and nonobese diabetic patients [31]. In our study, malnourished patients had lower BMI, which is consistent with most previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…However, in another study on Pima Indian people, retinopathy was relatively lower in patients with young- rather than later-onset T2DM[ 50 ]. In a recent meta-analysis, the most significant increase in the prevalence of T2DM was observed at more than 5 years after diagnosis[ 51 ]. Overall, available studies suggest that having younger onset T2DM increases the risk of retinopathy more than having T1DM of same duration, but the differences in risk between young-onset and usual onset T2DM remain unclear.…”
Section: Complications and Co-morbidities In Young-onset T2dmmentioning
confidence: 99%
“…D iabetic retinopathy (DR), one of the leading causes of irreversible blindness worldwide, is frequently accompanied by lens opacities [1][2][3][4] . Pars plana vitrectomy PPV combined phacoemulsification for PDR patients Int J Ophthalmol, Vol.…”
Section: Introductionmentioning
confidence: 99%